Colours : britannica discovery library - Maze, Stephanie (Encyclopaedia Britannica, Inc. Chicago, 2006)
This explores the rich world of colors, detailing their scientific foundations and cultural meanings. From the psychology of hues to their artistic applications, it reveals how colors influence perception and emotion.